2020
DOI: 10.1002/chem.202000587
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength‐Dependent Singlet Oxygen Generation in Luminescent Lanthanide Complexes with a Pyridine‐Bis(Carboxamide)‐Terthiophene Sensitizer

Abstract: Lanthanide ion (LnIII) complexes, [Ln(3Tcbx)2]3+ (LnIII=YbIII, NdIII, ErIII) are isolated with a new pyridine‐bis(carboxamide)‐based ligand with a 2,2′:5′,2′′‐terthiophene pendant (3TCbx), and their resulting photophysical properties are explored. Upon excitation of the complexes at 490 nm, only LnIII emission is observed with efficiencies of 0.29 % at 976 nm for LnIII=YbIII and 0.16 % at 1053 nm for LnIII=NdIII. ErIII emission is observed but weak. Upon excitation at 400 nm, concurrent 1O2 formation is seen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 96 publications
3
8
0
Order By: Relevance
“…Although we do not anticipate leaching of the metal ion from these complexes, control experiments using the LnCl 3 salts were conducted and confirmed that the free metal ions are not cytotoxic (Figures S34−S38), as previously observed. 33 ) for [Ln(nTdpa) 3 ] 3− (n = 1 or 2) in 95% Ethanol at 25.0 ± 0.1 The combined data suggest that these photosensitizers are potential photodynamic therapeutics with low dark toxicity. The cell death mechanism was studied by flow cytometry of HeLa cells stained with Annexin V-fluorescein isothiocyanate (FITC) and propidium iodide (PI) after incubating the cells with 12.5 μM of the 2Tdpa 2− -based compounds in the dark and after a short irradiation period of 5 min.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we do not anticipate leaching of the metal ion from these complexes, control experiments using the LnCl 3 salts were conducted and confirmed that the free metal ions are not cytotoxic (Figures S34−S38), as previously observed. 33 ) for [Ln(nTdpa) 3 ] 3− (n = 1 or 2) in 95% Ethanol at 25.0 ± 0.1 The combined data suggest that these photosensitizers are potential photodynamic therapeutics with low dark toxicity. The cell death mechanism was studied by flow cytometry of HeLa cells stained with Annexin V-fluorescein isothiocyanate (FITC) and propidium iodide (PI) after incubating the cells with 12.5 μM of the 2Tdpa 2− -based compounds in the dark and after a short irradiation period of 5 min.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These complexes are not water-soluble and are thus not viable for imaging and therapy applications in biological systems. More recently, we described a family of oligothiophene-based sensitizers of Ln III emission, which show wavelength-dependent 1 O 2 generation , but are also not water-soluble. Another series of oligothiophene-based ligands that were water-soluble were studied for their cytotoxicity toward HeLa cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some early reports focus on the construction of RE‐coordinated nanostructures with different compositions, morphologies, and applications. [ 146 ] Subsequently, the development of nanomaterials for bioimaging [ 85 , 86 , 90 , 147 ] and cancer theranostics [ 87 , 144 , 145 , 148 ] attracted increasing research interest. Jin et al reported an Nd integrated supramolecular polymeric nanoassembly to deliver siRNA and DOX for tumor therapy.…”
Section: Metal‐coordinated Supramolecular Self‐assemblies For Cancer Theranosticsmentioning
confidence: 99%
“…Moreover, it has been shown that the energy levels of the S n and T n states, and thus the ISC process [35], can be optimized by increasing the number of conjugated units, which is the basis of so-called "polymerization-enhanced photosensitization" concept [16,36,37]. Conjugated oligomers/polymers can be applied in the photosensitization of 1 O 2 either acting as photosensitizer itself or acting as the light-harvesting antennas or backbone to other PS molecules (e.g., dyes, fullerenes) [34,38,39]. In this review paper, the examples of both types of CP-based photosensitizers used in the medical applications, fine chemical synthesis or wastewater treatment-will be discussed.…”
Section: Introductionmentioning
confidence: 99%